Open Lesson as a Means of Teachers' Learning - Mustafa Abdulbakioglu; Anar Kolushpayeva; Nuri Balta; Nursultan Japashov; Christine L. Bae (MDPI AG, 2022)
Open lesson (OL), similar to the Japanese lesson study in many aspects, is a professional development model regularly used in schools in the Commonwealth of Independent States Countries. The purpose of this study was to examine teachers' and students' attitudes and beliefs about OL practices and activities, using both quantitative and qualitative methods. The sample consisted of 72 instructors and 239 university students in Kazakhstan. MANOVA results from teacher data and student data indicated weak positive attitudes and beliefs about OL. Moreover, no differences were found between the gender, discipline, nationality, and teaching experience of teachers, while students learning social sciences showed stronger positive attitudes and beliefs about the effect of OL on learning when compared to students learning natural sciences. Slightly positive attitudes and beliefs of participants imply that OL implementations in schools should be reconsidered.